Adaptations of the lexical-semantic level in nouns of Yoruba origin in practitioners of the complex Ocha-Ifá. Santa Clara (Islas, 2021)
The article analyzes a series of adaptations in nouns of Yoruba origin inserted in Cuban Spanish through the Lucumí legacy of practitioners of the Ocha-Ifá complex in Santa Clara at the lexical-semantic level. The methods and techniques used were: from the theoretical level: analytic-synthetic, inductive-deductive; from the empirical level: bibliographic review, interview, survey and observation. A predominance of stability (formal and semantic) was observed; phenomena related to the extension, reduction and change of meanings and relations of synonymy, antonymy, paronymy, homonymy and meronymy were identified among the corpus words. As conclusions, it was found that there is a high degree of adaptation to the characteristics of our national variant of the language from the contexts and social spaces that occupy the daily life of the practitioners.
Keywords: lexical-semantic level; nouns of Yoruba origin; Ocha-Ifá